Postoperative Combined Modality Treatment in High Risk Resected Locally Advanced Squamous Cell Carcinomas of the Head and Neck (HNSCC) - Kirtane, Kedar; Rodriguez, Cristina P. (Frontiers in Oncology, 2018)
Patients who undergo upfront curative intent resection for locally advanced squamous cell carcinomas and who have adverse pathologic features benefit from adjuvant therapy. Concurrent cisplatin based chemoradiation is an established standard of care endorsed by national guidelines. Controversy now exists on the applicability of this strategy to the good risk human papilloma virus related oropharynx cancer patient. Ongoing clinical studies are exploring therapeutic de-escalation in the postoperative setting for this distinct patient population. The introduction of immune checkpoint inhibitors to the therapeutic armamentarium for recurrent/metastatic head and neck cancer patients has led to clinical investigation of incorporation of PD-1 inhibition in the postoperative setting.